2020
DOI: 10.3390/su12030810
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Religious and Cultural Information of Olive Oil on Consumer Behavior: Evidence from Japan

Abstract: The olive tree and oil are iconic in the Mediterranean culture and religions, and producers incorporate those associations into the packaging of olive oil products they distribute regionally. This study examines the impact of religious and cultural information about olive oil on consumer behavior. A choice experiment was conducted to survey Japanese consumers’ willingness to pay for olive oil products. Results show that consumers respond with varying degrees of favor to the characteristic of “produced in pilgr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(15 citation statements)
references
References 44 publications
0
15
0
Order By: Relevance
“…This survey revealed that preference for an olive oil brand is correlated with brand awareness, and that it is positively correlated with recognition of the label, quality perception, and loyalty. Research on the impact of religious and cultural information about olive oils (Kitagawa et al, 2020) showed that Japanese consumers had a preference for Italian over Tunisian and Spanish olive oils, perhaps because they were familiar with Italy as the country of origin of olive oil. The rich cultural and religious background of the Mediterranean regions (largely Greco-Roman) is used to promote Mediterranean olive oils.…”
Section: Disconnect Between Consumer Preferences and Expert Evaluationmentioning
confidence: 99%
“…This survey revealed that preference for an olive oil brand is correlated with brand awareness, and that it is positively correlated with recognition of the label, quality perception, and loyalty. Research on the impact of religious and cultural information about olive oils (Kitagawa et al, 2020) showed that Japanese consumers had a preference for Italian over Tunisian and Spanish olive oils, perhaps because they were familiar with Italy as the country of origin of olive oil. The rich cultural and religious background of the Mediterranean regions (largely Greco-Roman) is used to promote Mediterranean olive oils.…”
Section: Disconnect Between Consumer Preferences and Expert Evaluationmentioning
confidence: 99%
“…Studies about the social aspect in sustainability labeling were merely present. Only 2 studies [107,108] were identified and their results confirmed consumer's sensitiveness to the rich cultural and religious unique background of the Mediterranean region and their great sense of trust towards olive oils family mills.…”
Section: Summary Of the Key Findingsmentioning
confidence: 96%
“…Moreover, Kitagawa et al [107] examined the effect of religious and cultural information on consumption behavior of olive oil. Results confirm the hypothesis that the rich cultural and religious unique background of the Mediterranean region makes it possible to differentiate the Mediterranean olive oil especially Greco-Roman images that are favorable to endorse olive oil among Japanese consumers.…”
Section: Consumers Attitudes and Behavior Regarding Social And Cultural Sustainability Labeling On Olive Oilmentioning
confidence: 99%
See 1 more Smart Citation
“…As Santong food products are required to conform to the corresponding quality standards of their export target markets, we expect that there are some similarities between the effect of the export target market and the region-of-origin (ROO) or country-of-origin (COO) effect. The impacts of ROO or COO on consumer preferences have been explored extensively [21][22][23][24][25]. ROO is an important quality cue, including information on product reliability and safety, which can reduce consumers' purchase risks [26,27].…”
Section: Background and Literature Reviewmentioning
confidence: 99%